Neonatal Outcomes in Very Preterm Singleton Infants Conceived Using Assisted Reproductive Technologies - Chiarelli, Laura; Mirea, Lucia; Yang, Junmin; Lee, Shoo K.; Shah, Prakesh S.; on behalf of the Canadian Neonatal Network (American Journal of Perinatology, 2015)
Objective To compare neonatal mortality, severe morbidities and hospital length of stay in very preterm singleton infants conceived using assisted reproductive technologies (ARTs) or spontaneously (SP).Study Design Singleton infants born at 23 to 32 weeks gestation during 2010–2012 were retrospectively identified from the Canadian Neonatal Network database. A composite outcome indicating a mortality or severe morbidity (grade ≥ 3 intraventricular hemorrhage, periventricular leukomalacia, stage ≥ 3 retinopathy of prematurity, bronchopulmonary dysplasia, or stage ≥ 2 necrotizing enterocolitis) was compared between ART and SP infants using multivariable logistic regression. Length of stay was examined in multivariable time-to-event analyses adjusting for competing risk of mortality.Results Eligible subjects included 346 (4.4%) ART and 7,578 (95.6%) SP infants. ART mothers were older, with fewer single parents, higher rates of nulliparity, diabetes, hypertension, antenatal corticosteroids, and prenatal care, but less smoking and substance use than SP mothers. No significant differences were detected in the composite outcome (odds ratio: 0.79; 95% confidence interval: 0.54–1.17) or length of stay (hazard ratio: 0.84; 95% confidence interval: 0.63–1.12) between ART and SP infants after adjustment for potential confounders and risk factors.Conclusion Among singleton infants born very preterm, mode of conception is not associated with overall mortality/morbidity or length of stay.
Keywords: fertility; mode of conception; singleton gestation; mortality; morbidities of prematurity